2019
DOI: 10.1177/1178622119837544
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Rainwater to the Irrigation Requirement for Paddy Cultivation at Tanore Upazila in Rajshahi, Bangladesh

Abstract: Groundwater extraction for irrigation in Bangladesh has caused groundwater depletion, especially in the Northern region. As such, shifting reliance from groundwater to surface water is one of the solutions to mitigate this problem. This study aims at investigating the contribution of effective rainfall to the total consumptive use requirement of rice cultivated in Tanore, Rajshahi, in Bangladesh. The prospect of rainwater harvesting using ponds and its contribution to the consumptive use requirement of rice wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, it is necessary to update the methods used to assess soil erosion processes and rates. It is also necessary to improve the management of agricultural lands (Al-Mossawi, 2014, Hasan et al, 2019. Nevertheless, there is a clear lack of information on the long-term soil redistribution in flood irrigated lands as most of the research is on short-term experiments (McElroy et al, 2018;Zuecco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is necessary to update the methods used to assess soil erosion processes and rates. It is also necessary to improve the management of agricultural lands (Al-Mossawi, 2014, Hasan et al, 2019. Nevertheless, there is a clear lack of information on the long-term soil redistribution in flood irrigated lands as most of the research is on short-term experiments (McElroy et al, 2018;Zuecco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al [20] found profitable horticultural production in hilly areas of Khagrachari district of Bangladesh using harvested rainwater. Rainwater harvested in Mini-Pond is being used to provide supplemental irrigation even for boro rice cultivation in northwestern drought prone areas of Bangladesh [21][22][23] where the altitude is much higher (11-48 m) than the coastal areas (0-2 m) but the amount of rainfall is much lower than the other parts of the country. Pandey and Biswas [24] showed through testing a robust water balance model in south-west region of Bangladesh that harvested rainwater through on-farm reservoirs during rainy season can be utilized for crop cultivation in the dry season.…”
Section: Photo Credit: Authormentioning
confidence: 99%
“…By the middle of the 21 st century, the sea level could have risen by 30 cm and rainfall in the dry season could have declined to 10.0 mm. Against the background of irrigation water scarcity, using cultivars with a short life cycle (Dang et al, 2021), shifting CCS (Dang, 2021), and water-saving irrigation (Hasan et al, 2019) are potentially effective adaptation solutions to ICV (Bai and Xiao, 2020). The objective of this study was to evaluate the impacts of rainfall, temperature, and irrigation water in coastal cultivation regions of Kien Giang Province.…”
Section: Introductionmentioning
confidence: 99%